Corn Cost-Return Budget in North Central Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2001)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_2001_10
Keywords: MF2161; Crops; Economics; MF